ДО ПИТАННЯ ПРО СУТНІСТЬ ЕКОНОМІЧНОГО ПРОСТОРУ - Butenko, T.O. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2010)
Philosophical, mathematical and geographical approaches to the space concept are analyzed. On this basis the definition of the economic space is formulated. Heterogeneity of the economic space has been proved logically. It is stated that heterogeneity is described by concentration, integration and convergence.